Implementasi Asesmen Formatif Terhadap Peningkatan Hasil Belajar Siswa di Mi Terpadu Mutiara Assyifa Kota Bengkulu - Sintia Parastika; Sofya Nadela; Salsadila Dwi Parica; Selvita Aryanti; Okki Wiranti (Yayasan Darussalam Bengkulu, 2024)
This study aims to describe the implementation of the Group 36 Teaching Assistance Program at MI Terpadu Mutiara Assyifa, Bengkulu City, and its impact on the learning process and student character development. The method used was descriptive qualitative, with data collected through observation, interviews, and documentation over 60 days of activity. Data analysis employed the Miles and Huberman model, encompassing data reduction, data presentation, and conclusion drawing. The results indicate that student intern involvement increased student activity and participation, enriched the variety of learning media, and supported teachers in classroom management. Students also demonstrated pedagogical, professional, personality, and social competencies, while adapting to the religious culture of the madrasah. Several innovations implemented, such as the Integrated Duty System, Teachers' Day Photobooth, and Educational Animation Games, had a positive impact on student discipline, learning motivation, and creativity. This study demonstrates that the Teaching Assistance Program plays a significant role in improving the quality of learning and serves as a vehicle for developing the competencies of prospective teachers.